Review: The Rise of Authoritarian in Political Behavior Many Countries - Dini Tiara Sasmi, Cifebrima Suyastri (UIR Press, 2022)
Question about which factors that influenced the rise of authoritarian in political behavior has been long discussion among academician. Many believes economy play a big role of how people choose to a certain political behavior. According to several recent studies, globalization play significant economic and political effects throughout the industrialized world. This paper seeks to answer the previous query based on article entitled “Economic Decline, Social Identity, and Authoritarian Values in the United States,” by Ballard-Rosa, et.al (2022), while also seek the strengths, and weaknesses from the readings and try to discover new research questions that arise from the article. They argue that long-term economic developments brought by globalization have a detrimental influence on traditionally dominant populations' social identities. Specifically, they suggest that changes in economic conditions and job status can cause shifts in authoritarian values, which is one way that globalization can contribute to people supporting extreme political candidates. This paper adds to literature revolving around authoritarian literature in at least three ways. To begin with, it throws new insight on the roots of populism and support for radical individuals and parties. Second, it gave new information on authoritarian beliefs' roots, which show that at least in part, authoritarian principles are susceptible to current economic and social situations. Third, the study emphasizes the necessity of comprehending how different forms of economic shocks may impact social identity and status, as well as political conduct.